Peliosanthes planicoronata (Asparagaceae), a new species from Southeastern Yunnan, China - Wang, Li Hong; Bi, Ming Hui; Chu, Hong Bo; Feng, Hui Zhe (Phytotaxa, 2024)
Peliosanthes planicoronata is described and illustrated as a new species from southern China. The new species is morphologically closest to P. khasiana N.Tanaka, differing in its triangular segments, smaller orifice of the corona, connate filaments and style which densely marked with purple spots and verrucose protrusions. Comparisons with other closely related species are also provided.